2021
DOI: 10.1021/acs.analchem.0c05118
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Near-Infrared Imaging of Peroxynitrite Fluxes in Inflammation Progress

Abstract: Inflammation is an important protection reaction in living organisms associated with many diseases. Since peroxynitrite (ONOO − ) is engaged in the inflammatory processes, illustrating the key nexus between ONOO − and inflammation is significant. Due to the lack of sensitive ONOO − in vivo detection methods, the research still remains at its infancy. Herein, a highly sensitive NIR fluorescence probe DDAO-PN for in vivo detection of ONOO − in inflammation progress was reported. The probe responded to ONOO − wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 62 publications
0
29
0
Order By: Relevance
“…(1.229 g, 85%). 1 Preparation of PMR. A mixture of compound 1 (1.2 g, 2.98 mmol), p-xylylene dichloride (5.15 g, 29.3 mmol), and K 2 CO 3 (0.2 g, 1.45 mmol) in 150 mL of CH 3 CN was refluxed and stirred for 12 h. After cooling the solution to room temperature and concentrating the obtained crude product in a vacuum drying oven to remove the solvent, the obtaining solid was purified by silica gel chromatography with the eluent dichloromethane and methanol (10:1, v/v) to afford solid PMR (0.414 g, 23%).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1.229 g, 85%). 1 Preparation of PMR. A mixture of compound 1 (1.2 g, 2.98 mmol), p-xylylene dichloride (5.15 g, 29.3 mmol), and K 2 CO 3 (0.2 g, 1.45 mmol) in 150 mL of CH 3 CN was refluxed and stirred for 12 h. After cooling the solution to room temperature and concentrating the obtained crude product in a vacuum drying oven to remove the solvent, the obtaining solid was purified by silica gel chromatography with the eluent dichloromethane and methanol (10:1, v/v) to afford solid PMR (0.414 g, 23%).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…A mixture of compound 1 (1.2 g, 2.98 mmol), p-xylylene dichloride (5.15 g, 29.3 mmol), and K 2 CO 3 (0.2 g, 1.45 mmol) in 150 mL of CH 3 CN was refluxed and stirred for 12 h. After cooling the solution to room temperature and concentrating the obtained crude product in a vacuum drying oven to remove the solvent, the obtaining solid was purified by silica gel chromatography with the eluent dichloromethane and methanol (10:1, v/v) to afford solid PMR (0.414 g, 23%). 1 H NMR (600 MHz, DMSO) δ 8.89 (s, 1H), 8.37 (d, J = 7.7 Hz, 2H), 8.17 knowledge, there are only two reports for detecting ONOO − and mitophagy, 33,43 one of which, the viscosity-based fluorescent probe from our research group, is used to simultaneously detect ONOO − and mitophagy, but which relies only on electrostatic attraction and is easily leaked from mitochondria in the process of mitophagy. Therefore, we are committed to the development of mitochondrial-immobilized fluorescent probes with a chloride group for the simultaneous detection of ONOO − and mitophagy.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a and S14a †), which were due to the ONOO − -promoted deprotection of diphenyl phosphonate group and hydrolysis of benzeneboronic ester. 43,47 Meanwhile, relative uorescent quantum yield(F F ) of BS1 and BS2 varied from 0.05% to 48.9% and from 0.03% to 42.7%, respectively, where the ethanolic solution of anthracene (F F ¼ 27%) was used as a ref. 51.…”
Section: The Optical Response Of Bs1 and Bs2 Toward Onoo −mentioning
confidence: 99%
“…[28][29][30][31][32] Recently, much efforts have been devoted to exploiting and designing novel uorescent ONOO − probes with excellent selectivity and sensitivity. From the recent reviews of uorescent chemosensors for ONOO − detection, it could be concluded that these uorescent ONOO − probes were developed based on the strong oxidation, nitration, and nucleophilicity of ONOO − , which usually incorporate some particular reactive moieties into different chromophores, such as alkene, 33,34 N-aminophenol, 35,36 active ketone, [37][38][39] arylboronic esters, [40][41][42][43] organoselenium/organotellurium 44,45 and diphenyl phosphonate unit. 46,47 Taking advantage of these reactive sites, the probes would release their masked uorescence upon attacked by ONOO − , which makes them promising biosensors for ONOO − detection and imaging.…”
Section: Introductionmentioning
confidence: 99%